Pengaruh Konsentrasi Ragi dan Metode Pemasakan Terhadap Karakteristik Fisikokimia dan Organoleptik Tapai Pisang Janten (Musa acuminata colla) - Putri, Ririn Chania; Marvie, Ilham; Wahyuningtyas, Amalia (Agriculture Faculty, 2024)
Tapai is a traditional food obtained from a fermentation process using yeast. The material used in the manufacture of tapai is a material that contains starch. One of the starchy ingredients that can be processed into tapai is the janten banana. Quality tapai has a distinctive taste, sweet and sour, producing an alcoholic aroma. Tapai quality can also be determined based on its physicochemical characteristics. Tapai fermentation is influenced by several factors, namely the yeast concentration and the cooking method used. This study aims to prove the effect of yeast concentration with various cooking methods on the physicochemical and organoleptic characteristics of Janten banana tapai. The yeast concentrations were 0.5% and 2%, while the cooking methods used were steaming and boiling. This experiment used a completely randomized design (CRD) with two factorials and two repetitions. The data were analyzed using a two-way ANOVA test with a level of =5%, and if there was a significant effect, then a DMRT follow-up test was carried out with a level of =5%. Treatment of 2% yeast concentration using the steam cooking method produced the best janten banana tapai with a texture value of 2.93 mm/g/s, 68.03% moisture content, 1.61% ash content, 3.25% alcohol content, pH 4 .78 and 25.55% total titrated acid.